Internet of Things (IoT) Based Temperature Monitoring System on The Low Voltage Sub-Distribution Panel (LVSDP) Busbar - Carlos R, Sitompul; Rumiasih; Indrawasih; Albianto, M. Dwi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
In this study, a tool is designed to monitor the temperature on the busbar of the Low Voltage Sub Distribution Panel (LVSDP) based on the Internet of Things. This tool uses the internet network to receive data from a sensor in real-time. The tool in this study is designed to detect the heat generated by the busbars of each phase installed in the LVSDP. Real-time display on the smartphone provides notification if the temperature on the busbar has exceeded the preset set point. To monitor the temperature on the busbar, real-time monitoring is needed which will make it more convenient for technicians to carry out maintenance. Monitoring the temperature on this busbar will be carried out by utilizing technology from IoT which will be connected to the internet and integrated with smartphone devices. In this study, the authors will use the ESP32 module as a medium for receiving, storing, and displaying data on smartphone devices. ESP32 is a module often used for IoT projects. Equipped with Wi-Fi and Bluetooth features and has a Dual-Core Microprocessor which will make data processing faster. To be able to receive temperature data, an infrared MLX90614 sensor is needed. The MLX90614 infrared sensor is an electronic component that functions to detect heat without touching the object whose heat is to be measured because this sensor is facilitated with infrared light which can be directed at the object.